The hot deformation behavior and microstructural evolution of as-cast Mg–2Zn–0.5Mn–0.2Ca–0.3Nd–0.7La alloy - Jie Mi; Deqing Ma; Shiyu Luan; Peipeng Jin; Lijia Chen; Xin Che; Xiaoqiang Li (Journal of Materials Research and Technology, 2023)
The microstructure and texture evolutions of the Mg–2Zn–0.5Mn–0.2Ca–0.3Nd–0.7La alloy were investigated by hot compression tests, which carried out in the temperatures range of 250–400 °C and strain rates range of 0.001–1 s−1. The thermal deformation behavior of the alloy was reflected by the hyperbolic sine function relationship, which was applicable to all stresses conditions due to the calculated value of α∗σp was 1.0. The thermal processing map based upon the dynamic material model was built. In addition, the suitable and unsuitable hot working regions were analyzed combined with microstructures. The results show that the dynamic recrystallization (DRX) mechanism of the hot compression deformation microstructure of the alloy was discontinuous dynamic recrystallization (DDRX). There were plenty of extension twins in some coarse deformed grains and these twins form a new <0001>//TD texture, which led to the weakening the <0001>//CD texture.